2020
DOI: 10.1088/1742-6596/1697/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

The shape of a vertical liquid bridge between arbitrary convex surfaces in axisymmetric case

Abstract: The article is devoted to the study of the lateral surface shape of a vertical liquid bridge of small volume between two arbitrary convex solid surfaces in the axisymmetric case. A variational statement of the original problem is given. The solution is found by the iteration method under the assumption that the Bond number is small. An algorithm for the iterative process is proposed, taking into account the action of gravity. It was found that the maximum number of different profiles of the lateral surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The conservation of volume is not limited to bubbles; it also applies to ink droplets, which has sparked debates in the printing industry regarding its impact on L * . Previous researchers [59][60][61][62][63] have studied the breakage of liquid stored between the gap of two horizontally and vertically separated rods. They observed that the volume of the liquid influenced L * ; however, their conclusions were affected by the movement of the contact line 64 during neck collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The conservation of volume is not limited to bubbles; it also applies to ink droplets, which has sparked debates in the printing industry regarding its impact on L * . Previous researchers [59][60][61][62][63] have studied the breakage of liquid stored between the gap of two horizontally and vertically separated rods. They observed that the volume of the liquid influenced L * ; however, their conclusions were affected by the movement of the contact line 64 during neck collapse.…”
Section: Introductionmentioning
confidence: 99%